2019
DOI: 10.1186/s12934-019-1231-9
|View full text |Cite
|
Sign up to set email alerts
|

Heterologous overexpression of bacterial hemoglobin VHb improves erythritol biosynthesis by yeast Yarrowia lipolytica

Abstract: Background Yarrowia lipolytica is an unconventional yeast with a huge industrial potential. Despite many advantages for biotechnological applications, it possesses enormous demand for oxygen, which is a bottleneck in large scale production. In this study a codon optimized bacterial hemoglobin from Vitreoscilla stercoraria (VHb) was overexpressed in Y. lipolytica for efficient growth and erythritol synthesis from glycerol in low-oxygen conditions. Erythritol is a natural sweetener produced by Y.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…In contrast to the previous experiment, Y. lipolytica was grown in a larger volume, and oxygen supply in the medium was better. Previously, it was shown that providing a high level of dissolved oxygen is crucial for efficient growth of Y. lipolytica [36]. The fermentation process took 120 h, and the obtained results of biomass production are shown in Figure 3 and Table 2.…”
Section: Shake-flask Experiments With Agricultural Waste Mediummentioning
confidence: 92%
“…In contrast to the previous experiment, Y. lipolytica was grown in a larger volume, and oxygen supply in the medium was better. Previously, it was shown that providing a high level of dissolved oxygen is crucial for efficient growth of Y. lipolytica [36]. The fermentation process took 120 h, and the obtained results of biomass production are shown in Figure 3 and Table 2.…”
Section: Shake-flask Experiments With Agricultural Waste Mediummentioning
confidence: 92%
“…Because the OTR decreases as the scale of the bioreactor increases, oxygen availability (OA) is a parameter difficult to master in bioreactor especially at large scale. Apart from classical modulation of impellers stirring speed and air flow inlet, this challenge has been addressed in many different bioprocessing and genetic engineering solutions (Mirończuk et al, 2019; Vandermies & Fickers, 2019). For example, increasing bioreactor pressure or utilization of perfluorodecalin as a second liquid phase result in an increase of OTR and thus of OA (Amaral et al, 2008; Lopes, Gomes, Mota, & Belo, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In another strategy, the increase in the cell's oxygen uptake rate was achieved by overexpression of VHb gene from Vitreoscilla , encoding a haemoglobin‐like protein. In Y. lipolytica , this has led to an improved cell growth capacity (Bhave & Chattoo, 2003) but also to higher productions of intracellular lipids (Zhang et al, 2019) or erythritol (Mirończuk et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Previously, researchers have showed that the heterologous expression of gene encoding the bacterial hemoglobin from Vitreoscilla stercoraria (VHb) can improve the oxygen utilization efficiency and further increase the productivity (Suen et al, 2014;Zhang et al, 2017). Recently, Mirończuk et al (2019) performed that the improved erythritol synthesis is obtained in Y. lipolytica, by overexpressing the codon-optimized bacterial hemoglobin (VHb). Through improving oxygen transfer rate using higher agitation rates or pure oxygen for aeration, the production of γ-decalactone was successfully enhanced (Moradi et al, 2013).…”
Section: Optimizing Fermentation Conditionsmentioning
confidence: 99%